Commentary: Poetry Is the Human Heart Speaking in Its Own Melody (LEARNing Landscapes, 2010)
In this interview Dr. Maya Angelou shares some early pivotal events and the important role her grandmother and brother played in supporting her spirit and encouraging her potential. She speaks of her strong conviction that poetry is essential, not only for students but also for everyone.She believes that reading poetry,which she feels should be read aloud, helps us to understand that we are not alone and that others have experienced and survived similar situations.The students in her poetry class bring what they learn to their respective disciplines because they come "to realize that nothing human should be alien to [them]."
Keywords: poetry; classroom; students; essential; reading poetry